A 'PASEO' Approach: Regionally contextualized and integrated engagement, dialoguing, knowledge sharing and communication - Schuetz, Tonya; Waldorf, Abby (2014)
In research for development (R4D) and programmatic research work for development knowledge sharing and knowledge management, engagement and networking is essential for achieving behavioral change. R4D is about making sure research is contributing to positive development agendas and changes. We need to engage and communicate internally within our projects with the potential users of our results who can influence and implement change. It is important to clearly distinguish—from the beginning—the difference between this ‘internal communication’, what we will refer to as the ‘paseo approach’, and corporate communications. This document will elaborate the key characteristics/principles/good practices of what we aim for in internal project communications, the ‘paseo approach’, and what it requires in terms of processes, competencies and skills in the people who undertake it.